2001
DOI: 10.1038/sj.ijo.0801704
|View full text |Cite
|
Sign up to set email alerts
|

Clinical aspects of obesity in childhood and adolescence—diagnosis, treatment and prevention

Abstract: The level of fatness at which morbidity increases is determined on an acturial basis. Direct measurements of body fat content, eg hydrodensitometry, bioimpedance or DEXA, are useful tools in scientific studies. However, body mass index (BMI) is easy to calculate and is frequently used to define obesity clinically.An increased risk of death from cardiovascular disease in adults has been found in subjects whose BMI had been greater than the 75th percentile as adolescents. Childhood obesity seems to increase the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0
6

Year Published

2003
2003
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 29 publications
(31 reference statements)
0
33
0
6
Order By: Relevance
“…A obesidade nas crianças é decorrente de muitos fatores, tais como dieta pobre e inatividade física 17 . Estudos prévios demonstraram que, se um dos pais ou ambos forem obesos, o risco de a criança se tornar obesa na idade adulta aumenta de 3-10 vezes 15 .…”
Section: Introductionunclassified
“…A obesidade nas crianças é decorrente de muitos fatores, tais como dieta pobre e inatividade física 17 . Estudos prévios demonstraram que, se um dos pais ou ambos forem obesos, o risco de a criança se tornar obesa na idade adulta aumenta de 3-10 vezes 15 .…”
Section: Introductionunclassified
“…Both obesity and eating disorders (ED) are problems with substantial health consequences and are highly resistant to treatment (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12) . ED are serious mental disorders, with a clear chronic tendency and high co-morbidity with other mental disorders, highly resistant to treatment and associated with adverse medical conditions (1,3,5) .…”
Section: Prevalence Of Eating-and Weight-related Problemsmentioning
confidence: 99%
“…The 1999-2000 National Health and Nutrition Examination Survey (NHANES) found that 15.5% of 12-19-year-olds and 15.3% of 6-11-year-olds are overweight, defined as a body mass index (BMI) exceeding the 95th percentile for age and gender [1]. Child and adolescent overweight are associated with a myriad of medical and psychosocial consequences [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%